2013
DOI: 10.1159/000354966
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Erythematosus Cells in Bone Marrow: The Only Clue to a Previously Unsuspected Diagnosis of Systemic Lupus Erythematosus

Abstract: Background: Systemic lupus erythematosus (SLE) is an autoimmune multisystem disease characterized by the development of antinuclear antibodies. Nowadays considered outdated, lupus erythematosus (LE) cell preparation served as a screening test for SLE for decades. However, the importance of discovering LE cells on routine cytology cannot be overemphasized. Case: We report the case of a 30-year-old female in whom bone marrow aspiration (BMA) was performed during an investigative workup for pyrexia of unknown ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In these cases, bone marrow biopsies may sometimes be performed in lieu of autoantibody testing to rule out malignancy or bone marrow failure. 5 Pujani et al 9 concluded that the unexpected observation of LE cells in BMA films can allow for the diagnosis of unsuspected cases of SLE. In addition, they mentioned two novel insights: First, LE cells can rarely be detected in BMA films prepared immediately without the use of anticoagulants, incubation, or any other manipulation, and that they are an exceptional finding; and second, they reported that accurate cytological observation of BMA samples can provide crucial clues to previously unsuspected conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, bone marrow biopsies may sometimes be performed in lieu of autoantibody testing to rule out malignancy or bone marrow failure. 5 Pujani et al 9 concluded that the unexpected observation of LE cells in BMA films can allow for the diagnosis of unsuspected cases of SLE. In addition, they mentioned two novel insights: First, LE cells can rarely be detected in BMA films prepared immediately without the use of anticoagulants, incubation, or any other manipulation, and that they are an exceptional finding; and second, they reported that accurate cytological observation of BMA samples can provide crucial clues to previously unsuspected conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, this neutropenia is mild, has little impact on disease, and requires no specific treatment. 8,9 Any pathogenesis beyond this condition is related to accelerated apoptosis of mature neutrophils. 8 Antineutrophil antibodies have been implicated in this process; however, these can also be present in some patients with SLE without neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Searching through publications, we found only 1 case report in which LE cells were detected in the fresh bone marrow specimen without anticoagulant from an adult patient with fever of unknown origin, resulting in the diagnosis of unsuspected SLE [11]. It was believed that LE cells could only be seen in the fresh bone marrow without anticoagulant [11]. We report here the case of a pediatric patient who presented with weight loss, depression, and cytopenia without clinical suspicion of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of LE cells in bone marrow and body fluids in previous reports has prompted the testing of autoantibodies and resulted in the diagnosis of unexpected SLE. [8][9][10][11][12][13] In our recent case report, 14 LE cells were identified in the bone marrow aspirate of an adolescent girl who was thought to have anorexia nervosa and depression. The bone marrow biopsy was performed to rule out leukemia, suspected due to anemia and neutropenia.…”
Section: Introductionmentioning
confidence: 89%